2016
DOI: 10.1021/acs.orglett.6b02458
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Multisite-Selective Acetoxylation Reactions at sp2 vs sp3 C–H Bonds in Cyclic Olefins

Abstract: The first Pd-catalyzed multisite-selective acetoxylation reactions are disclosed at an unactivated alkene sp C-H bond versus secondary allylic sp C-H bond in cyclic olefins via the modulation of directing groups. The different directing groups overcome the key challenge in differentiating C-H bonds and provide a new controlling approach for site-specific C-H activation. A wide variety of substrates are readily acetoxylated under operationally simple conditions. Mechanistic studies suggest that different Pd (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…6 Accordingly, it is highly desirable to synthesize new compounds possessing these substructure moieties for drug discovery. To continue our research in palladium-catalyzed C−H activation, 7 herein we report the development of an intramolecular Fujiwara− Moritani/oxidative Heck cyclization to synthesize spirodihydroquinoline and octahydrophenanthrene derivatives employing the same palladium catalytic system.…”
mentioning
confidence: 99%
“…6 Accordingly, it is highly desirable to synthesize new compounds possessing these substructure moieties for drug discovery. To continue our research in palladium-catalyzed C−H activation, 7 herein we report the development of an intramolecular Fujiwara− Moritani/oxidative Heck cyclization to synthesize spirodihydroquinoline and octahydrophenanthrene derivatives employing the same palladium catalytic system.…”
mentioning
confidence: 99%
“…Also, copper-free conditions led to the moderate yield (entry 3), which demonstrated that Cu­(OAc) 2 ·H 2 O as an oxidant can effectively regenerate the Pd­(II) catalyst from Pd(0). Moreover, PhI­(OAc) 2 serving as an oxidant in the Pd­(II)/Pd­(IV) catalytic cycle greatly reduced the yield (entry 4), which demonstrated that this reaction differentiating from previous research could prefer a Pd(0)/Pd­(II) catalytic cycle. Additionally, removal of base or using acids such as HOAc and PivOH, which can boost the palladium catalysis, , showed unsatisfactory results (entries 5–7).…”
Section: Resultsmentioning
confidence: 68%
“…Loh et al and Bi et al reported alkylation of γ-C­(alkenyl)–H, and Engle et al recently published elegant alkenylation of β or γ-C­(alkenyl)–H, utilizing different bidentate auxiliaries (Scheme A) . Notably, picolinamide (PA) as a removable directing group facilitated remote site-selective functionalization of the C­(alkenyl)–H bond such as arylation at the γ-position, alkenylation and iodination at the δ-position at a distance of three methylenes from PA, and acetoxylation at the δ-position (Scheme B). However, only E -selective δ-C­(alkenyl)–H alkenylation of aminoethyl cycloalkenes with PA as a remote bidentate directing group has not been documented. Thus, inspired by the above literature and previous work, , we report an efficient method for the synthesis of cycle-containing dienes starting from cycloalkenes bearing PA and electron-deficient alkenes to generate corresponding only E -products (Scheme C).…”
Section: Introductionmentioning
confidence: 99%
“…The protocol of diastereoselective Pd( ii )-catalyzed, DG-aided C–H functionalization has been extended to assemble cis olefins via Z selective C(sp 2 )–H-functionalization. 5,86,87 Babu reported 86 a the diastereoselective Pd( ii )-catalyzed, AQ-aided β-C(sp 2 )–H arylation of acrylamide 72a with ArI to afford the Z -cinnamamide 72b 86 a , b (Scheme 37). Xu/Loh and Besset have demonstrated the Z selective β-C(sp 2 )–H alkylation, 86 c and chlorination 86 e of substrate 72a to afford the corresponding products 72k and 72l .…”
Section: Miscellaneous Examples: Diastereoselective C(sp2)–h Function...mentioning
confidence: 99%